Gut Microorganisms of Aquatic Animals 2.0 - Kormas, Konstantinos Ar (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This is a collection of scientific research articles focusing on the associations and/or interactions of various aquatic animals with their microorganisms, focusing mostly on fish and, in particular, gut bacterial communities.